Possibilities of using biogas in agriculture - Bolyssov, T.K.; Zhanybayeva, Z.K.; Yessengeldin, B.S.; Tuleubayeva, M.K. (KSU Publ., 2019)
The article discusses the possibilities of using agricultural waste for biogas production. The authors pay great attention to domestic and foreign practice of generating energy using biogas plants. According to the authors, the use of biogas as an integral part of renewable energy sources will have positive economic and environmental effects in agriculture: reduction of greenhouse gases; recycling; job creation; increased energy security. The authors determined the prospects for the use of biogas industry products in agriculture: it allows you to get ready-to-use mineral fertilizers with a high content of nitrogen and phosphorus component; increases the intensity of agriculture due to the availability of cheap heat and electricity. The article highlights the main advantages of using biogas in agriculture: the widespread availability of raw materials in the form of agricultural waste; flexibility in the marketing and use of bioenergy in rural areas. The authors made recommendations on the development of biogas energy in agriculture: development of a state program for the development of biogas energy; opening of centers of expert and engineering consulting the implementation of biogas energy projects; the creation of several state agricultural enterprises for the production of biogas in different regions of the country.
Ауыл шаруашылығында биогазды қолданудың мүмкіндіктері
Возможности использования биогаза в сельском хозяйстве
Keywords: agriculture; biogas; biomass; bioenergy; biogas industry; biogas plants; agricultural waste